Determinants of Sexual Violence at Sexual Debut against in-School Adolescents in Ghana - Tenkorang, Eric Y. (Journal of family violence, 2021)
Very few studies examine sexual violence perpetrated on adolescents in Ghana or in sub-Saharan Africa more generally. Using data collected in 2015 as part of a multi-country initiative, we employed multinomial logit models to examine violence experienced by Ghanaian adolescents at sexual debut. Results of our gender-specific models showed violence at sexual debut is gendered. While adolescent girls reported higher levels of forced sex (rape) at sexual debut, boys reported higher levels of coercion. Compared to those who had sex at relatively older ages, girls who had sex at younger ages were significantly more likely to say they were raped, were coerced or that sex ‘just happened’ than to report sex was wanted. Both male and female adolescents were significantly more likely to report sex was forced than wanted if the sexual partner was older. Female respondents who lived with family members other than their parents were significantly more likely to report forced sex (rape). We recommend government and interested stakeholders to promote social norms that discourage violence against adolescents. School-based programs, such as Ghana’s comprehensive sexuality education, must focus on equipping adolescents with the confidence and skills required to handle cultural pressures and the power differences that characterize sexual relationships.